(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Fingerprints are one of the most effective methods of identification. However lip prints can also provide important information. At the present time more and more people use protecting lipsticks and permanent lipsticks. With these lipsticks a latent lip print is generated by contact with a surface and, like with the latent fingerprints occur, this latent lip print can be developed. In a previous work the use of lysochromes, specifically Sudan III, Oil Network Or and Sudan Black, was used for the development of latent lip prints on porous and non porous surfaces, is proposed. These reagents are very effective even for old latent lip prints . But when prints are left on very dark or multicoloured surfaces, some problems of contrast may hide the development. The work that follow study the usefulness of fluorescent reagents to develop latent lip prints on very dark or multicoloured surfaces. Preliminary analysis have demonstrated the efficiency of Nile Red to develop old prints on different dark colour surfaces (specifically blue, red and black). Current research tests the usefulness of fluorescent reagents on both multicoloured and dark coloured surfaces.